Provincial inequalities in life cycle carbon dioxide emissions and air pollutants from electric vehicles in China - Dingding Hu; Kaile Zhou; Rong Hu; Jingna Yang (Communications Earth & Environment)
Abstract It is still unclear whether emissions reductions from electric vehicles can be achieved across different regions from a lifecycle perspective. Here we use the life cycle assessment model and Quasi Input-Output model to evaluate the carbon dioxide emissions and air pollutants of internal combustion engine vehicles, plug-in hybrid electric vehicles, and battery electric vehicles in different provinces of China, with the provincial electricity consumption data and the sales data of electric vehicles. We find that battery electric vehicles have achieved 11.8% and 1.1% reduction in carbon dioxide and nitrogen oxide emissions, respectively, compared to internal combustion engine vehicles. In contrast, the emissions of sulfur dioxide and particulate matter 2.5 increased by 10% and 20%, respectively. Due to the coal-based power generation structure and the cold weather, the emission intensity of battery electric vehicles in most northern provinces is higher than that in southern provinces. From 2020 to 2030, improving technological progress and optimizing electricity mix will greatly assist in achieving emissions reduction. The results can help policy-makers better understand the emission characteristics and reasonably plan future emission reduction strategies in transportation.